UME6 Is Involved in the Suppression of Basal Transcription of ABC Transporters and Drug Resistance in the ρ+ Cells of Saccharomyces cerevisiae - Yoichi Yamada (Microorganisms, 2022)
In Saccharomycescerevisiae, the Rpd3L complex contains a histone deacetylase, Rpd3, and the DNA binding proteins, Ume6 and Ash1, and acts as a transcriptional repressor or activator. We previously showed that RPD3 and UME6 are required for the activation of PDR5, which encodes a major efflux pump, and pleiotropic drug resistance (PDR) in ρ0/− cells, which lack mitochondrial DNA. However, there are inconsistent reports regarding whether RPD3 and UME6 are required for Pdr5-mediated PDR in ρ+ cells with mitochondrial DNA. Since PDR5 expression or PDR in the ρ+ cells of the rpd3Δ and ume6Δ mutants have primarily been examined using fermentable media, mixed cultures of ρ+ and ρ0/− cells could be used. Therefore, we examined whether RPD3 and UME6 are required for basal and drug-induced PDR5 transcription and PDR in ρ+ cells using fermentable and nonfermentable media. UME6 suppresses the basal transcription levels of the ABC transporters, including PDR5, and drug resistance in ρ+ cells independent of the carbon source used in the growth medium. In contrast, RPD3 is required for drug resistance but did not interfere with the basal PDR5 mRNA levels. UME6 is also required for the cycloheximide-induced transcription of PDR5 in nonfermentable media but not in fermentable media.